QTL mapping and genomic selection of stem and branch diameter in soybean (Glycine max L.) - Wang, Jing; Yang, Qichao; Chen, Yijie; Liu, Kanglin; Zhang, Zhiqing; Xiong, Yajun; Yu, Huan; Yu, Yingdong; Wang, Jun; Song, Jian; Qiu, Lijuan (Frontiers in Plant Science, 2024)
Soybean stem diameter (SD) and branch diameter (BD) are closely related traits, and genetic clarification of SD and BD is crucial for soybean breeding. The results showed that SD and BD were significantly correlated (r = 0.74, P < 0.001). A total of 93 and 84 unique quantitative trait loci (QTL) were detected for SD and BD, respectively, using the restricted two-stage multi-locus genome-wide association, inclusive composite interval mapping, and three-variance component multi-locus random SNP effect mixed linear modeling, based on an recombinant inbred line population of 363 individuals constructed by a cross between Zhongdou41 (ZD41) and ZYD02878. There were two and ten major QTLs for SD and BD, respectively, with phenotypic variance explained (PVE) by more than 10%. Within these loci, seven genes involved in the regulation of phytohormones (IAA and GA) and cell proliferation and showing extensive expression of shoot apical meristematic genes were selected as candidate genes. Genomic selection (GS) analysis showed that the trait-associated markers identified in this study reached 0.47–0.73 in terms of prediction accuracy, which was enhanced by 6.56–23.69% compared with genome-wide markers. These results clarify the genetic basis of SD and BD, which laid solid foundation in regulation gene cloning, and GS models constructed could be potentially applied in future breeding programs.